The Relationship between the Timing of a Self-Efficacy Questionnaire, Duration of Training, and Levels of Self-Efficacy with Patient-Centered Interviewing Skills. Issue 1 (2nd January 2021) - Walling, Brandon M.; Smith, Sandi W.; Grayson-Sneed, Katelyn; Smith, Robert C.
ABSTRACT: There are conflicting findings about the role that timing plays in the administration of self-efficacy questionnaires and the relationships between self-efficacy scores, training, and subsequent demonstration of skills. The current study examined self-efficacy in the context of a training program to educate residents in patient-centered communication skills. Previous research indicates that providers who use patient-centered skills have higher patient satisfaction ratings and their patients show improved physical and psychological health outcomes. 163 residents conducted patient-centered interviews with standardized patients. One group rated their self-efficacy before the interview ( n = 85, 52%) and the other group rated it after the interview ( n = 78, 48%). Researchers used a validated content analysis coding scheme to measure patient-centered skills in the interviews. There was no significant difference in self-efficacy scores obtained before or after the interview or in the relationship between self-efficacy and objectively coded patient-centered skills in either group. Self-efficacy also did not mediate the relationship between training in patient-centered skills and significantly improved performance of the skills. The findings suggest that timing of self-efficacy questionnaire does not influence subsequent self-efficacy ratings and that demonstrated PCI skills and perceived self-efficacy ratings increase significantly with training. Results imply that self-efficacy requires further study before it can be used as a surrogate for skills performance.